A Critical Examination of the Distribution of BSI CSR Funds for Sports Activities in Aceh - Insani, Muhammad Fitrah; Maulana, Muhammad (Institut Agama Islam Negeri Madura, 2025)
The concept of Corporate Social Responsibility (CSR) is a form of corporate social obligation aimed at making a positive contribution to surrounding communities. Every company, in its operations, inevitably causes various impacts, both ecological and socio-economic, in the area where it operates. In this context, the study critically examines the policy of distributing CSR funds by Bank Syariah Indonesia (BSI) for sports activities in Aceh, especially its contribution to professional football clubs. Using a qualitative descriptive approach and SWOT analysis, the study reveals that BSI’s CSR allocation is not fully aligned with the principles of long-term social benefit. Key findings highlight weak community involvement, lack of transparency, and the absence of an effective program evaluation system. On the other hand, great opportunities to empower youth and local communities through inclusive sports programs have not been optimally utilized. Strategic recommendations include shifting CSR focus from professional sports to community-based empowerment and enhancing accountability and public participation mechanisms. The results emphasize the need to reformulate CSR policies to better reflect sustainability values, comply with sharia principles, and provide tangible impacts on social welfare.